TRENDS IN ROMANIA'S TOURISM DEMAND AND OFFER IN THE MOUNTAIN RESORTS DURING THE PERIOD 2010-2019 - Agatha POPESCU; Alina MARCUTA; Liviu MARCUTA; Cristina TINDECHE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper analyzed the dynamics of tourist demand and offer in Romania's mountain resorts in the period 2010- 2019 using the statistical data collected from National Institute of Statistics in order to identify the main trends and suggest solutions for enhancing this sector of the national tourism. Fixed basis index, structural index and comparison method have been used for data processing. Romania has more than 100 mountain resorts, with a wonderful scenery and breathtaking splendors and treasure which must be discovered. More than 95 resorts are suitable for skiing. The most attractive mountain resorts are Poiana Brasov, Sinaia, Busteni, Predeal, Azuga, Paltinis, Vatra Dornei, Ranca and Transalpina. Over 2.3 million tourists spent their vacations in Romania's mountain resorts in 2019, being 2.8 times more then 2010 and accounting for 17.2% of total Romania's visitors. Romanians are dominant with a share of 91%. Not only the number of Romanians is growing up, but also the foreign visitors number which reached over 196 thousand in 2019, that is 2.2 times more than in 2010. The overnight stays increased 2.8 times, accounting for 4.42 million in 2019. In the mountain resorts there are 2,370 units for tourists accommodation, of which about 70% were represented by tourist and agro-tourist guesthouses, 8.7% tourist villas, 7.9% hotels and 6.2% chalets etc. Their number represent 27.5% of Romania's tourism accommodation units. In 2019, the offer of places (beds) was 63,943, by 80.4% more than in 2010 and representing 17.8% of the total offer in Romania's tourism. The beauty of the natural mountain landscapes, biodiversity, local economy, humans, cultural and historical heritage have to be better valorized, developed and promoted to enhance mountain tourism to increase its efficiency and competitiveness. Mountain skiing resorts have to continue their efforts to improve the access roads, buildings, equipments, installations, facilities, to enlarge the range of activities and to offer to tourists unforgettable vacations and to entirely cover their expectations.